Socioeconomic inequalities in health behaviors in children and adolescents: evidence from an Australian cohort - Nirmal Gautam; Mohammad Mafizur Rahman; Rasheda Khanam (BMC Public Health)
Abstract Background Understanding the association between socioeconomic inequalities and health behaviors is imperative for elucidating and effectively addressing health inequities among children and adolescents. Despite the wealth of literature on social gradients in health behaviors, longitudinal analyses of socioeconomic inequalities in the health behaviors of children and adolescents are relatively limited, particularly in the Australian literature. Therefore, this study aimed to investigate the association between socioeconomic inequalities and health behaviors among Australian children and adolescents. Methods This study utilized the secondary data from the Longitudinal Study of Australian Children (Waves 2–8), which included participants aged 2 to 15 years. Relative index inequality (RII) methods were used to investigate the associations between socioeconomic inequalities and the health behaviors of children and adolescents. Results Compared with their counterparts, children and adolescents with high socioeconomic status (SES) are 84% more likely to consume fruits and vegetables (RII = 1.84, 95% CI = 1.63–2.09) and 19% less likely to consume sugary beverages (RII = 0.81, 95% CI = 0.77–0.86), but more likely to consume sweet and savory foods (RII = 1.09, 95% CI = 1.01–1.19). Children and adolescents with high SES were less likely to spend their free time on screens (RII = 0.86, 95% CI = 0.81–0.91) and more inclined toward outdoor activities (RII = 1.75, 95% CI = 1.53–1.98). Conclusion This study provides useful insight into socioeconomic inequalities and health behavior outcomes in children and adolescents. These findings stress the need for tailored interventions designed to improve the health behaviors of families from lower socioeconomic backgrounds. Additionally, addressing unhealthy dietary behaviors, such as the higher consumption of sweet and savory foods among children from higher SES backgrounds, is equally critical. Such comprehensive interventions have the potential to reduce socioeconomic disparities in health behaviors and improve the well-being of the broader population.